Subwavelength negative index planar terahertz metamaterial arrays using spiral split ring resonators for near field sensing - Naeem, Nadeem; Ismail, Alyani; Alhawari, Adam Reda Hasan; Mahdi, Mohd Adzir (IOS Press, 2015)
This study reports new shape of meta-material array structures having electric and magnetic resonances designed for terahertz (THz) frequency band. The proposed structures exhibit left handed meta-material propertiesin THz frequency band. The introduced meta-material split ring resonators in this paper are constructed using a single loop of conducting wire strip printed over a very thin low permittivity polyimide dielectric substrate. The effective parameters like permeability and negative index are extracted from the simulated complex scattering parameters using direct retrieval method. Unloaded Q-factor is calculated for proposed terahertz metamaterial resonators. The proposed arrays are tested by loading different dielectric samples in order to confirm the testing capability. Significant shift in the transmission is observed. The reported array structures are novel in terms of their left handed behavior in THz frequencies. High values of Q-factor reported here, are suitable for near field sensing applications.